The Aragonese rural school in intercultural contexts: a basic of social justice and territorial equity in resilient Spain - Domingo Cebrián, Virginia; Nolasco Hernández, Alberto; Lorenzo Lacruz, Juan; Gracia Sánchez, Laura (Frontiers in Education, 2025)
The main characteristics of rural schools include their intercultural context and diversity, making them an inclusive reference. This diversity fosters positive relationships between the school and its environment, enhancing the teaching-learning process. This article presents partial results from a project by the Ministry of Science and Innovation of Spain titled “Rural schools: a basic service for social justice and territorial equity in sparsely populated Spain” (PID2020-115880RB-100). Using stratified random sampling with proportional allocation, 101 rural schools in Aragon participated, represented by 61 teachers who provided data through the “Rural school and territorial dimension” questionnaire. The questionnaire gathered information on various educational projects implemented in collaboration with other institutions to promote territorial development and address the challenges and needs of rural areas. The results showed that 90.1% of the projects focus on developing collective identity and a sense of belonging, providing services to the community, fixing and/or rooting the population, and responding to shared needs. These findings highlight the role of rural schools in cultural integration, inclusion, and specific support to ensure that all students and their families feel valued and an integral part of the community.